TRANS ORAL ENDOSCOPIC THYROIDECTOMY VESTIBULAR APPROACH (TOETVA), CASE SERIES OF THE FIRST CLINICAL EXPERIENCE FROM PAKISTAN - Iqra Zakir; Ahmad Nawaz (Journal of Ayub Medical College Abbottabad, 2023)
Background: The objective of the study to assess the workability and cosmetic outcome of endoscopic thyroidectomy vestibular approach (TOETVA) and share results of underdeveloped country with the world about their first clinical experience. Methods: We performed TOETVA in 3 patients presenting with thyroid nodules in our hospital, between October 2020 and December 2020 at Liaquat National hospital. Three-port technique was used, one 10-mm port for camera and two 5-mm ports for working. All ports were passed through oral vestibule. The demographic data of the patients and surgical outcomes were retrospectively reviewed. The surgery was completed successfully in all 3 patients. The operative time was between 120-150 mins. Results: No complications such as recurrent laryngeal nerve palsy, mental nerve injury or parathyroid gland injury damage occurred in patients postoperatively. No visible scarring occurred in the patients postoperatively. Patients remain stable after surgery and got discharged next day. No complications were noted in 6 months follow up. Conclusion: TOETVA is safe, feasible, effective and scar free option as compared to conventional thyroid surgery.